Muscle activation patterns of the upper and lower extremity during the windmill softball pitch - Oliver, G. D.; Plummer, H. A.; Keeley, D. W. (The Journal of Strength and Conditioning Research, 2011)
Fast-pitch softball has become an increasingly popular sport for female athletes. There has been little research examining the windmill softball pitch in the literature. The purpose of this study was to describe the muscle activation patterns of 3 upper extremity muscles (biceps, triceps, and rhomboids [scapular stabilizers]) and 2 lower extremity muscles (gluteus maximus and medius) during the 5 phases of the windmill softball pitch. Data describing muscle activation were collected on 7 postpubescent softball pitchers (age 17.7 ± 2.6 years; height 169 ± 5.4 cm; mass 69.1 ± 5.4 kg). Surface electromyographic data were collected using a Myopac Jr 10-channel amplifier (RUN Technologies Scientific Systems, Laguna Hills, CA, USA) synchronized with The MotionMonitor™ motion capture system (Innovative Sports Training Inc, Chicago IL, USA) and presented as a percent of maximum voluntary isometric contraction. Gluteus maximus activity reached (196.3% maximum voluntary isometric contraction [MVIC]), whereas gluteus medius activity was consistent during the single leg support of phase 3 (101.2% MVIC). Biceps brachii activity was greatest during phase 4 of the pitching motion. Triceps brachii activation was consistently >150% MVIC throughout the entire pitching motion, whereas the scapular stabilizers were most active during phase 2 (170.1% MVIC). The results of this study indicate the extent to which muscles are activated during the windmill softball pitch, and this knowledge can lead to the development of proper preventative and rehabilitative muscle strengthening programs. In addition, clinicians will be able to incorporate strengthening exercises that mimic the timing of maximal muscle activation most used during the windmill pitching phases.